Analisis Urf’ Terhadap Tradisi Appasumbang Doe Sebagai Piutang Dalam Perkawinan di Kecamatan Bontoramba Kabupaten Jeneponto - Maryam, St; Arsyad, Azman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
The research that will be examined by the author is the urf' analysis of the appasummbang doe tradition as a marriage receivable in Tanammawang Village, Bontoramba District, Jeneponto Regency. This study aims to describe the comparative analysis of Islamic law and positive law on the urf' analysis of the appasummbang doe tradition as a marriage receivable in Tanammawang Village, Bontoramba District, Jeneponto Regency). This type of research is qualitative research. The research location is in Tanammawang Village, Bontoramba District, Jeneponto Regency. The focus of the research is the urf' analysis of the appasummbang doe tradition as a marriage receivable in Tanammawang Village, Bontoramba District, Jeneponto Regency. In this study, the determination of informants was carried out using purposive sampling. Data collection techniques used in this study are observation, in-depth interviews, and documentation. As well as data analysis techniques in this study using data analysis and interactive models, namely by reducing data, presenting data, and verifying or drawing conclusions.The results showed that in the analysis of urf' (habits) in traditional marriage, this is a tradition that has been inherent in the community in the village of plantingmawang since 1984 until now, this custom is carried out at weddings, circumcisions, building houses etc. In this custom of money donations, the way to return it is by exceeding what the community received previously or in the term multiplied, of course this custom has a positive impact and a negative impact, but there are more positive impacts because the purpose of the establishment of this custom is to help ease the burden on the people who do it. party and help each other